CURRENT TRENDS IN INTERNATIONAL BUSINESS - Evgeny V. Ryabinin (Статистика и экономика, 2016)
The methodological bases of researchof international business are stated in the article. The great attention is focused on analysis of main trends in development of international. The comparison of competitiveness to of most used forms ofinternational business, as well as identiﬁed the main problems and barriers of theinternational business structures.